Translation of Ambiguous Syntactic Structures: Suggested Solution Difficulties - Udhruh, Esraa Abdullah Ahmed Ali et al. (University of Science and Technology, Sana'a, Faculty of Humanities and Social Sciences, Translation Program, 2025)
Syntactic ambiguity occurs when a sentence can be interpreted in multiple ways due to its grammatical structure, presenting significant difficulties for translators. This study aims to investigate the size of difficulty resulting from this area, the classification of the difficulties and to suggest solutions that may enhance translating syntactically ambiguous structures from English into Arabic. Besides, it tries to attest whether there is a significant correlation between syntactic ambiguity translation and gender variable. The research focuses on third-year BA students enrolled in the Translation Program at the University of Science and Technology, Hodeidah. Employing a descriptive and analytical approach and utilizing a translation test instrument, the study evaluated students' proficiency in translating 15 syntactically ambiguous sentences, followed by both qualitative and quantitative analyses. The results indicate that the majority of students experienced Moderate difficulty (54.2%), a smaller proportion faced Low difficulty (41.7%) and a few encountered High difficulty (4.2%). Furthermore, the findings revealed that students tend to offer a single interpretation (45.8%), while fewer provided two correct interpretations (36.7%), and some produced inaccurate translations (17.5%). No significant correlation was found between gender and translation performance. The study recommends enhancing training on ambiguity resolution and incorporating strategies such as contextual analysis and disambiguation techniques. This research contributes to improving translation practices and offers valuable insights for future studies in translation challenges.